Spinal schistosomiasis masquerading as spinal cord tumor in a 12-year-old male adolescent: A case report - Gashaw Arega; Leul Adane; Eden Mekonnen; Michael A. Negussie (Radiology Case Reports)
Spinal schistosomiasis, a rare manifestation of schistosomal infection, can closely mimic the presentation of spinal cord tumors and pose significant diagnostic challenges. We present the case of a 12-year-old boy from northern Ethiopia who experienced progressive back pain, tingling sensations in his lower extremities, and intermittent fever. Initially referred with a presumptive diagnosis of myxopapillary ependymoma for pediatric hematology-oncology evaluation, his marked eosinophilia and history of swimming in local rivers raised suspicion for spinal schistosomiasis. Upon review by a neuroradiologist, an MRI revealed a long-segment expansion of the spinal cord from T10 to L2, showing heterogenous enhancement on T1-weighted postcontrast images and hyperintense signals on T2-weighted images. Furthermore, the patient's Schistosoma mansoni IgG titer was elevated, strongly supporting the diagnosis. Treatment was initiated with praziquantel and corticosteroids, leading to a notable improvement in his symptoms. This case highlights the importance of considering parasitic infections like schistosomiasis in regions where they are endemic, particularly when spinal pathologies may resemble neoplastic conditions. Early diagnosis and intervention are crucial to preventing long-term neurological damage.